The Creation of Artists and Audiences in Morna Pearson’s The Artist Man and the Mother Woman (2012) - Beck, András (Hungarian Journal of English and American Studies, 2020)
This essay explores Northeast Scotland-born Morna Pearson’s first full-length play, The Artist Man and the Mother Woman (2012), a grotesque portrait of a tortured relationship of a middle-aged artist-teacher and his troubled mother. As Pearson’s dark comedy gradually turns into a violent tale of horror, new semantic dimensions unfold from beneath the initial surface of light entertainment, among them the exploration of the nature of artistic creativity. The sources of this creativity lie in belated sexual awakening and the powers this process unleashes. The essay argues that due to the representation of the liminal artist figure both as a creator and as a creation, Pearson’s Künstlerdrama studies the creation of art and the creation of the artist as intertwined processes which are difficult to distinguish. (AB)